2006
DOI: 10.1002/syn.20292
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor signaling molecules are altered in elderly schizophrenic cortex

Abstract: Alterations of molecules that mediate dopaminergic signal transduction have been found in schizophrenia, supporting the hypothesis of altered dopaminergic neurotransmission in this illness. To further explore this hypothesis, the authors measured transcript expression of three proteins involved in dopamine (DA) signaling in postmortem dorsolateral prefrontal and anterior cingulate cortex of elderly schizophrenic subjects and a comparison group. The transcript encoding calcyon, a protein that potentiates crosst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 51 publications
3
25
0
3
Order By: Relevance
“…For example, decreased DARPP-32 was detected in the frontal cortex and thalamus (Albert et al, 2002;Feldcamp et al, 2008;Ishikawa et al, 2007;Torres et al, 2009;Zhan et al, 2011), whereas transcripts for calcyon and spinophilin, mediators of dopaminergic signal integration, were increased in the thalamus in schizophrenia (Baracskay et al, 2006;Clinton et al, 2005). Additionally, phosphorylation of the N-methyl-D-aspartic acid (NMDA) receptor type 1 subunit at S897, a target of PKA, is decreased in the frontal cortex, suggesting fewer NMDA receptors at the synapse (Emamian et al, 2004;Tingley et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased DARPP-32 was detected in the frontal cortex and thalamus (Albert et al, 2002;Feldcamp et al, 2008;Ishikawa et al, 2007;Torres et al, 2009;Zhan et al, 2011), whereas transcripts for calcyon and spinophilin, mediators of dopaminergic signal integration, were increased in the thalamus in schizophrenia (Baracskay et al, 2006;Clinton et al, 2005). Additionally, phosphorylation of the N-methyl-D-aspartic acid (NMDA) receptor type 1 subunit at S897, a target of PKA, is decreased in the frontal cortex, suggesting fewer NMDA receptors at the synapse (Emamian et al, 2004;Tingley et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Examinations of spinophilin mRNA expression have yielded mixed results. Elevations in spinophilin mRNA across all cortical layers in PFC were reported in one study (Baracskay et al, 2006), whereas no change expression has been reported in anterior cingulate cortex in the same subjects (Baracskay et al, 2006) and in thalamus from the same brain tissue collection (Clinton et al, 2005). A study of PFC in a different cohort found no change in spinophilin mRNA expression in subjects with schizophrenia (Weickert et al, 2004).…”
Section: Interpretive Issuesmentioning
confidence: 93%
“…One report found that DARPP-32 protein abundance was selectively reduced in the prefrontal cortex of brain tissue from patients with schizophrenia (19), and 1 recent report found no significant difference in mRNA levels in brains from 16 elderly schizophrenic patients compared with matched controls (20). However, given the central role of the protein in molecular mechanisms related to dopaminergic neurotransmission in striatum and its diverse pharmacological actions, we hypothesized that it would be associated in humans with higher-level cognitive and emotional behaviors implicated in cortical-striatal circuitry and function and contribute genetically to variation in these functions.…”
Section: Introductionmentioning
confidence: 98%